Assessment of neuropsychiatric symptoms in dementia: validity and reliability of the Lebanese version of the neuropsychiatric inventory questionnaire. Issue 5 (3rd September 2021) - Feghali, Yara; Fares, Youssef; Abou Abbas, Linda
Abstract: This study aims to examine the psychometric properties of an Arabic version of the Neuropsychiatric Inventory Questionnaire (NPI-Q) that evaluates neuropsychiatric symptoms in patients with dementia. A cross-sectional study was carried out with a sample of 136 Lebanese demented patients aged 63–98 years. NPI-Q was completed by the patients' primary caregiver and standard NPI was administered through personal interview by an experienced research assistant to the same caregiver. The internal consistencies of the Arabic NPI-Q total and distress scale were 0.680 and 0.684 respectively. One week test-retest reliability of the total NPI-Q and distress scores were 0.991 and 0.988 respectively ( p -value <0.0001 for both). The NPI-Q correlated significantly with the standard NPI in individual and total symptom scores as well as caregiver distress scores. Exploratory factor analysis extracted five factors that explained 64.7% of variances. The prevalence of analogous symptoms reported on the NPI and NPI-Q differed on average by 3% while moderate or severe symptom ratings differed on average by 1%. The Arabic version of the NPI-Q showed evidence of good psychometric properties indicating that it is a suitable tool for the routine assessment of neuropsychiatric symptoms for Lebanese patients with dementia in clinical settings.